Analisis Pengaruh Dana Bantuan Pembangunan dalam Rangka Mengurangi Ketimpangan Pendapatan di Provinsi Jawa Barat - Armi Bakar; Rizal Rahmawan (LITERATUS, 2021)
This study aims to prove the effectiveness of development assistance funds in reducing income inequality. However, the results of the study show that development assistance funds do not affect income inequality. Regression analysis with secondary data was used in this study. In dealing with data that are not normally distributed, researchers perform data transformations with natural logarithms. The researchers found other closely related variables related to income inequality in the discussion, namely education, health, and the industrial sector.